(3YfGUQ GdeRjL GdJShjbj YHQ GdGfJQfJs - (3jhSa CMeO(B, (3CHh aGRIs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2007)
(3GdGYeGd GdEdcJQhfjI(B- (3fXGe GdeYdheGJ GdJShjbjI ddGYeGd GdEdcJQhfjI(B- (3GdefGaSI Hjf efXeGJ GdCYeGd YHQ GdCfJQfJ(B- (3NOeGJ GdRHhf hYedjGJ GdShb hGdTQGA YHQ GdCfJQfJ(B- (3GdJShjb GdEdcJQhfj(B- (3JNWjW hJWhjQ GdefJLGJ YHQ GdCfJQfJ(B- (3SYQ GdefJLGJ GdeHGYI YHQ GdCfJQfJ(B- (3JUeje GdehbY(B- (3GdJhRjY GdEdcJQhfj YHQ GdGfJQfJ(B- (3GdJQhjL GdEdcJQhfj YHQ GdGfJQfJ(B- (3GdeLJeYGJ GdEaJQGVjI(B- (3GdJNUjU(B- (3GdNhUUI(B- (3Cef GdCYeGd GdEdcJQhfjI(B.s
(3GdedGMb U(B.383s
Keywords: (3COGQI GdeHjYGJs; (3GdGfJQfJs; (3GdJShjbs